Reawakening the Irish Language through the Irish Education System: Challenges and Priorities - T.J. Ó CEALLAIGH; Áine Ní DHONNABHÁIN (International Electronic Journal of Elementary Education, 2015)
As a language, Irish is unique to Ireland and is, therefore, of crucial importance to the identity of the Irish people, to Irish culture and to world heritage. The Irish language however has had a turbulent and traumatic history and has endured a complex and varied relationship with the Irish people. Since the foundation of the Irish Free State, the education system has been targeted as an agency and model for Irish language planning, education and language revitalisation and has had a critical role in generating linguistic ability in the Irish language. This paper reviews the complex and controversial relationship between the Irish language, the State and the education system from an historical perspective. Some key acts of recent legislation and government initiatives, which impact on the status of the Irish language are considered and barriers and challenges to progress in the education system are outlined. The paper concludes with a discussion on significant positive factors which may revolutionise and reawaken the Irish language through our education system.